African Sculptures and Forms = Sculptures et formes d'Afrique - Neyt, François 1939-; Dubois, Hughes (Five Continents Editions, 2018)
At the turn of the twentieth century, in particular Gauguin, Picasso, Matisse and later the Surrealists, then others right up till the present day, Western artists have drawn on the arts of Africa for inspiration. How can this constant impact ever be measured? The same is true for the arts in Africa. Every sculpture carries within it the heritage of a people, culture and artistic tradition in the originality of its forms. West Africa, Central Africa and East Africa each has its own set of characteristics, within which the variety of the sculptures - always similar yet also always different - demonstrates the creativity of the ethnic group that created it. This book presents a remarkable collection amassed by a knowledgeable and impassioned art lover that combines sensitivity with quality - a quality of forms meticulously selected among different African cultures. It includes masks and reliquaries carved in Gabon, effigies and statuettes from Congo-Brazzaville and Congo-Kinshasa, and astonishing objects from West Africa, from Mali to Cameroon, the Koro and Mossi peoples, the Ejagham and Ekoi in Nigeria and the Gouro in the Ivory Coast. An extraordinary collection of artistic forms that well merits its place in the universal patrimony of art